Ananlysis of Carbon Emission Reduction and Power Dominance between Single Manufacturer and Single Retailer in Regulatory Cap and Trade System - Liang-jie Xia; Hua-wei Zhi (Discrete Dynamics in Nature and Society)
In the cap and trade system, the paper analyses the Stackelberg game between the power asymmetrical retailer and manufacturer and designs a side-payment self-enforcing contract to resolve some arguments that the existing research overemphasizes spontaneity of participation in side-payment contracts design based on supply chain coordination and does not consider rationality and fairness of allocation of profit increment. Also, the numerical analysis was given. The research shows some important conclusions: in the supply chain, the dominant manufacturer is not able to encourage the retailer to improve its promotion level by increasing its carbon cutting level, but the optimal emission reduction level increases with the dominant retailer’s promotion level; the optimal promotion level, emission reduction, and product demand in a retailer leading supply chain are higher than those in a supply chain dominated by manufacturer; with the new side-payment self-enforcing contract, decentralized decision according to individual rationality incurs a collective reason effect in the centralized setting.